Making sense of an historic landscape - Rippon, Stephen 1968- (Oxford Oxford University Press, 2012)
This volume explores how the archaeologist or historian can understand variations in landscapes. Making use of a wide range of sources and techniques, including archaeological material, documentary sources, and maps, Rippon illustrates how local and regional variations in the 'historic landscape' can be understood.
Includes bibliographical references and index.
Keywords: Electronic books; Landscape archaeology -- England -- Black Down Hills; Black Down Hills (England) -- Antiquities